Automated fan speed control based on room temperature using Arduino Mega2560 / Ahmad Mustaqim Zayadi - Zayadi, Ahmad Mustaqim (2019)
This project focus on development of automated fan speed controlled based on room temperature using Arduino Mega2560. Hence, this project proposes the detection the people motion to switch ON and OFF fan automatically and also to controlled speed of fan based on room temperature using Arduino Mega2560, IR and PIR sensor, motor driver L298N, humidity and temperature sensor (DHT11), liquid crystal display and fan 12VDC. The usability of an Arduino Mega2560 in this project is to develop a program that are controlling all the system automatically. This project help solves the problem to control speed of fan manually and to reduce the power consumption when user forget to switch OFF the fan. This project will give the solution for all sort of problem because this project automated all of this function to ease the user to switch ON and OFF the fan and to control speed of fan automatic. With this project, the user no need to worry about when forget to closed the fan because this project will switch OFF the fan. For this prototype, the system is developed to only to detect human motion using IR and PIR sensor. This system is developed based on the room at the house. However, this project also helps the user to change the speed of fan and switch ON and OFF fan successfully done. As a result, this project automated fan speed controlled based on room temperature using Arduino Mega2560 is successfully implemented.